Palliative radiotherapy in patients with metastases to the back bone due to prostate cancer and bladder cancer - Karczewska, Aldona; Adamiak, Ewa; Stryczyńska, Grażyna; Bączyk, Maciej; Milecki, Piotr; Stachowski, Tomasz; Cieślikowski, Wojciech; Leppert, Wojciech; Kwias, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2002)
Introduction: Bone metastases are a common feature of advanced cancer disease and are considered to be among the most frequent causes of pain and complications in oncological patients. The main objective of the treatment of such patients is to control their symptoms and improve the quality of their life. This paper was aimed to evaluate a short-course radiotherapy as the pain management in a group of patients with low performance status (ECOG> or = 2) and short life expectancy. Material and methods: The records of patients who developed bone metastases to the back bone with pain symptoms and/or early symptoms of spinal cord compression were evaluated. 118 patients were treated at our departments between 1997 and 2001. The diagnosis of primary disease were as follows: prostate cancer (108 out of 118 pts) and bladder cancer (10 out of 118 pts). All patients underwent only X-ray therapy (a daily fractionation 4,0 Gy, total dose 20 Gy) in conjunction with analgesics (NSAID ±opioids) and a low dose of dexamethasone (4-8 mg/d, p.o.). During the follow-up all patients received bisphosphonates, mainly pamidronate. Patients recorded pain severity on the visual self assessment scale (VAS) and analgesic requirements before the radiotherapy treatment, at the end of the treatment and during the follow-up. Changes in the neurological status and mobility skills were also evaluated. Analgesic and decompression effects were described together as "complete", "moderate" and "absent or progression". Results: The median survival of the patients from the beginning of the treatment was 6.5 months. The median intensity of pain before the treatment according to the VAS scale was 7 (range of 4-10). After the treatment the decrease of pain intensity by 3 on the 10 points VAS scale was noted. At the same time, the reduction of analgesic medications intake by 50% was observed. The mean motor activity of patients before irradiation was evaluated as 3 (range of 2-4) according to ECOG the scale. The fatal progression of symptoms of spinal cord compression resulting in the paresis was observed only in 5 out of 118 (4%) patients. A second spinal radiation therapy (second course of radiation) was necessary in 21 cases due to the ineffective first course. The decompression effects were noted as follows: "complete" in 37 out of 118 (31%) patients "moderate" in 66 out of 118 (56%) patients and "absent or progression" in 15 out of 118 (13%) patients. We observed a few side effects of the treatment (mild nausea and vomiting). Conclusions: A short-course radiotherapy treatment is safe and efficient in the early phase of spinal cord compression in patients with low performance status and short life expectancy. It is worth that such to underline treatment is short and convenient which is important to patients with relatively short survival.